Prognostic Factors Associated with Resected Osteosarcoma: Efficacy of Adjuvant Setting, Real-World Experience - ŞİMŞEK, FATİH; SEVER, NADİYE; KOCAASLAN, ERKAM; EREL, PINAR; ARIKAN, RUKİYE; SARI, MURAT; BAYOĞLU, İBRAHİM VEDAT; KÖSTEK, OSMAN (My University, 2024)
Osteosarcoma is a curable tumor. Surgery is performed after neoadjuvant chemotherapy as the primary standard treatment, followed by adjuvant therapy again. However, it is seen in patients who have undergone surgery without neoadjuvant chemotherapy. Adjuvant treatment is always given in this group. However, it is controversial how many cycles of adjuvant treatment should be given. In our study, 42 patients with osteosarcoma who received only adjuvant treatment without neoadjuvant treatment were analyzed for the effects of epidemiologic factors, treatment regimens on overall survival and disease-free survival. Retrospectively, 42 osteosarcoma patients (5 centers) with a current age of 18years and older who were followed up between 2001-2022 were examined. Twenty-five (60.0%) were below 8 cm, and 16 (38.0%) were 8 cm and above. The median number of cycles of adjuvant chemotherapy was 4 (range; 1-6). The 4-year DFS rate was 50.2%. In patients with primary tumors smaller and larger than 8cm, the 4-year DFS rates were 66.1% and 22.2%, respectively. The 4-year DFS rates for patients with 4 or less and more than 4 cycles of adjuvant chemotherapy were 27.1% and 69.2%, respectively. The 4-year OS rate was 78.5% in patients with primary tumors smaller than 8 cm and 18.8% in patients with tumors larger than 8 cm. The 4-year OS rate was 24.3% in patients who received 4 or less adjuvant cycles and 79.5% in patients who received more than 4 cycles. We have demonstrated that the number of adjuvant therapy courses above 4 and the presence of primary tumors smaller than 8 cm are influential over overall and disease-free survival in the patients who did not receive neoadjuvant therapy. The number of postoperative adjuvant treatment cycles should be forced as much as possible in these patients who haven’t had neoadjuvant therapy.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Oncology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMATOLOJİ; ONKOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEMATOLOGY; ONCOLOGY; Adjuvant therapy; Disease-free survival; Osteosarcoma; Overall survival